Phloem unloading via the apoplastic pathway is essential for shoot distribution of root-synthesized cytokinins. Issue 4 (27th April 2021) - Zhao, Jiangzhe; Ding, Bingli; Zhu, Engao; Deng, Xiaojuan; Zhang, Mengyuan; Zhang, Penghong; Wang, Lu; Dai, Yangshuo; Xiao, Shi; Zhang, Cankui; Liu, Chang-Jun; Zhang, Kewei
Abstract: Root-synthesized cytokinins are transported to the shoot and regulate the growth, development, and stress responses of aerial tissues. Previous studies have demonstrated that Arabidopsis ( Arabidopsis thaliana ) ATP binding cassette (ABC) transporter G family member 14 (AtABCG14) participates in xylem loading of root-synthesized cytokinins. However, the mechanism by which these root-derived cytokinins are distributed in the shoot remains unclear. Here, we revealed that AtABCG14-mediated phloem unloading through the apoplastic pathway is required for the appropriate shoot distribution of root-synthesized cytokinins in Arabidopsis. Wild-type rootstocks grafted to atabcg14 scions successfully restored trans-zeatin xylem loading. However, only low levels of root-synthesized cytokinins and induced shoot signaling were rescued. Reciprocal grafting and tissue-specific genetic complementation demonstrated that AtABCG14 disruption in the shoot considerably increased the retention of root-synthesized cytokinins in the phloem and substantially impaired their distribution in the leaf apoplast. The translocation of root-synthesized cytokinins from the xylem to the phloem and the subsequent unloading from the phloem is required for the shoot distribution and long-distance shootward transport of root-synthesized cytokinins. This study revealed a mechanism by which the phloem regulates systemic signaling of xylem-mediated transport of root-synthesized cytokinins from the root to the shoot. Abstract : Phloem unloading via the apoplastic pathway is essential for shoot distribution and long-distance translocation of root-synthesized cytokinins from the root to the shoot through the xylem.